A business process reengineering case study at AZAM Travel - Hashim, Mohd Zahrin; Ahmad, Hartini; Jilal, Johari (Academy for Global Business Advancement (AGBA), 2015)
The first computer-based reservation systems were operated by airlines.However, in the 1970s, some airlines began to provide access to selected travel agents.A growing demand for tourism brought new requirements for technology, and this trend continues today (Dabas and Manaktola 2007). The tourist industry relies heavily on access to information and its dissemination.Therefore, the effective use of information technology (IT) is pivotal.New IT systems are being developed and rapidly diffused through the industry.The impacts are far reaching, and no players in tourism can escape the need to embrace IT in their business activities It is therefore essential that IT can supply an appropriate infrastructure that can facilitate key functions in the tourism industry (Kracht and Wang, 2009).A global distribution system (GDS) is the portal that travel agents use to make reservations for flights, hotels, vehicle rental, and other travel service bookings. In addition to providing travel agency reservation services, a GDS can also provide access to information about pricing and availability to on-line travel agencies, and extend the reservation functionality on-line.GDS enables automated transactions to be conducted over a corporate network, and in the tourism industry this involves vendors and booking agents who provide travel-related services to consumers (Wang, 2010).The consumer is able to access a GDS via the internet, and carry out research into services provided by travel service providers worldwide.Consumers can access various global distribution systems and purchase tickets from a variety of flight providers and airlines. Global competition has driven organizations to become leaner and more streamlined. Many organizations have turned to business process reengineering (BPR) as a means to radically change the way they conduct business. BPR theories enable organisation to, for example, analyse their marketing operations and see how they cross-cut more than one of their business units (Thao and Swierczek 2008).A typical scenario is that information systems which were built for carrying out a specific function are obsolete, because new processes have been introduced and previously segregated processes have since been integrated.BPR is concerned with identifying and restructuring corporate management and can encompass legal, ownership, operational and other structures, with the aim of making the business more profitable or better able to meet current needs (Wang, 2010).In the tourism industry, travel agents are particularly affected by changing technologies which they must utilise, in order to provide quality services that meet consumer demands (Gazzoli, Kim & Palakurthi, 2007).The aim of this study is to investigate whether or not the use of the internet improves the services the industry provides through the adaptation of one of GDS.If there is no improvement in revenues and levels of service by using the internet, then it is important to be aware of the situation and adjust investment and BPR processes accordingly.